In planta gene expression analysis of Xanthomonas oryzae pathovar oryzae, African strain MAI1 - Soto Suárez, M.; Bernal, D.; González, C.; Szurek, B.; Guyot, R.; Tohme, Joseph M.; Verdier, Valerie M. (Springer, 2010)
Background: Bacterial leaf blight causes significant yield losses in rice crops throughout Asia and Africa. Although both the Asian and African strains of the pathogen, Xanthomonas oryzae pv. oryzae (Xoo), induce similar symptoms, they are nevertheless genetically different, with the African strains being more closely related to the Asian X. oryzae pv. oryzicola (Xoc).